Synergy as a new and sensitive marker of basal ganglia dysfunction: A study of asymptomatic welders - Lewis, Mechelle M. (Neurotoxicology, 2016)
BACKGROUND: Multi-digit synergies, a recently developed, theory-based method to quantify stability of motor action, are shown to reflect basal ganglia dysfunction associated with parkinsonian syndromes. In this study, we tested the hypothesis that multi-digit synergies may capture early and subclinical basal ganglia dysfunction. We chose asymptomatic welders to test the hypothesis because the basal ganglia are known to be most susceptible to neurotoxicity caused by welding-related metal accumulation (such as manganese and iron). METHODS: Twenty right-handed welders and 13 matched controls were invited to perform single- and multi-finger pressing tasks using the fingers of the right or left hand. United Parkinson’s Disease Rating Scale and Grooved Pegboard scores were used to gauge gross and fine motor dysfunction, respectively. High-resolution (3T) T1-weighted, T2-weighted, T1 mapping, susceptibility, and diffusion tensor MRIs were obtained to reflect manganese, iron accumulation, and microstructural changes in basal ganglia. The synergy index stabilizing total force and anticipatory synergy adjustments were computed, compared between groups, and correlated with estimates of basal ganglia manganese [the pallidal index, R1 (1/T1)], iron [R2* (1/T2*)], and microstructural changes [fractional anisotropy and mean diffusivity]. RESULTS: There were no significant differences in Unified Parkinson’s Disease Rating Scale (total or motor subscale) or Grooved Pegboard test scores between welders and controls. The synergy index during steady-state accurate force production was decreased significantly in the left hand of welders compared to controls (p=0.004) but did not reach statistical significance in the right hand (p=0.16). Anticipatory synergy adjustments, however, were not significantly different between groups. Among welders, higher synergy indices in the left hand were associated significantly with higher fractional anisotropy values in the left globus pallidus (R=0.731, p<0.001) but not with the pallidal index, R1, or R2* values in the basal ganglia. CONCLUSIONS: These data suggest that multi-digit synergy metrics may serve as preclinical markers for basal ganglia dysfunction in welders and other populations at risk for neurodegenerative diseases involving parkinsonian symptoms. This finding may have important clinical, scientific, and public/occupational health implications.